Perioperative Oral decontamination and ImmunoNuTrition (POINT) to prevent postoperative pulmonary complications in elderly patients scheduled for elective non-cardiac surgeries: protocol for a multicentre, randomised controlled trial - Jing Zhang; Yuguang Huang; Wen Wang; Yuelun Zhang; Xiaochun Zheng; Lu Che; Junping Chen; Lan Yao; Jiawen Yu; Lining Huang; Qianmei Zhu; Lichi Xu; et al. (BMJ Open)
Introduction Elderly patients are known to be vulnerable to postoperative pulmonary complications (PPCs), especially pneumonia. Apart from elder age, preoperative pulmonary diseases, anaemia, malnutrition, dysphagia and frailty may all be contributing factors to PPCs. Poor oral hygiene is a risk factor for PPC as well, as oropharyngeal microflora might be introduced to the lower respiratory tract following endotracheal intubation for general anaesthesia during surgery. Immune regulation, nutrition supplementation and improvement of oropharyngeal microflora might regulate immune and stress response and can be beneficial to elderly patients exposed to surgical stress. In this study, we will explore the effects of perioperative oral decontamination and immunonutrition supplementation on the incidence of postoperative pneumonia in high-risk elderly surgical patients.Methods and analysis This study is a multicentre, two-by-two factorial randomised controlled trial evaluating the efficacy of immunonutrition supplementation and oral chlorhexidine decontamination. A total of 592 patients aged 65 years and older who are scheduled for elective non-cardiac surgeries in seven tertiary hospitals in China will be recruited. Patients will be excluded if they have contraindications to the intervention. Patients will be randomised into four groups in a 1:1:1:1 ratio (oral decontamination vs routine oral care, immunonutrition supplementation vs routine nutrition advice). The primary outcome is the incidence of PPCs within 7 days after surgery. The secondary outcomes are the incidence of postoperative pneumonia, infectious complications, Comprehensive Complication Index, postoperative functional recovery, length of hospital stay and hospital expenses. Intention to treat principles will be applied to all outcomes. Descriptive analysis will be used to compare patients’ baseline characteristics. Logistic regression will be used to compare the incidence of PPCs within 7 days after surgery between different groups.Ethics and dissemination The study protocol has been approved by the Research Ethics Committee of Peking Union Medical College Hospital (I-23PJ953). All participants will provide written informed consent. Study results will be published in peer-reviewed journals and presented at academic conferences.Trial registration number NCT05971810.